Hubungan Religiusitas Dengan Motivasi Belajar Pendidikan Agama Islam Siswa - Zaida, Nuraini (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
This research was motivated by the lack of hours of Islamic Religious Education subjects which resulted in students having knowledge that was not optimal. In addition, the conditions at that time, which was still a pandemic, affected the learning process which was not optimal. With some of these problems can reduce motivation to learn. Religiosity is maturity in understanding, living and applying the noble values of religion which can potentially increase students' learning motivation. The results of the calculation of the hypothesis test show that the average value for Religiosity is 82.825, for Learning Motivation in Islamic Religious Education is 77.155, the Correlation coefficient is +0.219, the coefficient of determination is 47.961% or rounded up to 48% as the contribution of the Religiosity variable with Motivation to learn. The result of calculating the product moment correlation coefficient is known that rcount rtable (0.219 0.1996) with a significance level of 5%, then the hypothesis Ha is accepted and Ho is rejected. From these calculations it is clear that there is a significant relationship between Religiosity and Learning Motivation in Islamic Religious Education for Class X Students of Al-Washliyah Private Vocational School, Marbau, North Labuhanbatu Regency.